Do you say what you hear? Perception-production link of a phoneme contrast in Singapore Mandarin - Goh, Hannah Letitia (2023)
Existing studies have suggested that there may be a link between perception and production of speech sounds. In this paper we examine this link using data collected on Singapore English-Mandarin bilingual adults. We used a 2AFC task to measure perception of the Singapore Mandarin [tsʰuə́n]-[ʈʂʰuə́n] alveolar-retroflex contrast, and measured production using centre of gravity (CoG) measurements on speech recordings of alveolar and retroflex words. We found that a perception-production link may exist in our participants, with participants who exhibit less retroflexion in speech showing less sensitivity to retroflexion in ambiguous speech sounds.